Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress. (June 2023) - Wang, Lei; Lin, Mo; Hou, Xin; Dou, Liangding; Huang, Zhi; Liu, Rong; Zhang, Jinwen; Cai, Chuchu; Chen, Chen; Liu, Ying; Wang, Dai; Guo, Dongbei; et al.
Abstract: Purpose: The board application of black phosphorus quantum dots (BP-QDs) increases the risk of inhalation exposure in the manufacturing process. The aim of this study is to explore the toxic effect of BP-QDs on human bronchial epithelial cells (Beas-2B) and lung tissue of Balb/c mice. Methods: The BP-QDs were characterized using transmission electron microscopy (TEM) and a Malvern laser particle size analyzer. Cell Counting Kit-8 (CCK-8) and TEM were used to detect cytotoxicity and organelle injury. Damage to the endoplasmic reticulum (ER) was detected by using the ER-Tracker molecular probe. Rates of apoptosis were detected by AnnexinV/PI staining. Phagocytic acid vesicles were detected using AO staining. Western blotting and immunohistochemistry were used to examine the molecular mechanisms. Results: After treatment with different concentrations of BP-QDs for 24 h, the cell viability decreased, as well as activation of the ER stress and autophagy. Furthermore, the rate of apoptosis was increased. Inhibition of ER stress caused by 4-phenyl butyric acid (4-PBA) was shown to significantly inhibit both apoptosis and autophagy, suggesting that ER stress could be an upstream mediator of both autophagy and apoptosis. BP-QD-induced autophagy can also inhibit the occurrence of apoptosis using molecules related to autophagy including rapamycin (Rapa), 3-methyladenine (3-MA), and bafilomycin A1 (Bafi A1). In general, BP-QDs activate ER stress in Beas-2B cells, which further induces autophagy and apoptosis, and autophagy may be activated as a factor that protects against apoptosis. We also observed strong staining of related proteins of ER stress, autophagy, and apoptosis proteins in mouse lung tissue following intracheal instillation over the course of a week. Conclusion: BP-QD-induced ER stress facilitates autophagy and apoptosis in Beas-2B cells and autophagy may be activated as a protective factor against apoptosis. Under conditions of ER stress induced by BP-QDs, The interplay between autophagy and apoptosis determines cell fate. Graphical abstract: Image 1 Highlights: Repeated infusion of BP-QDs for a week resulted in lung injury to mice. BP-QD-induced ER stress facilitates autophagy and apoptosis in Beas-2B cells. 4-PBA can partly resist autophagy and apoptosis induced by BP-QDs. Defective autophagy or dysfunction of autophagic flux promotes cell apoptosis. Autophagy may be activated as a protective factor against apoptosis.